Cat8 Response to Nutritional Changes and Interaction With Ehrlich Pathway Related Factors - Du, Zhengda; Deng, Hong; Cheng, Yanfei; Zhai, Zhiguang; Guo, Xuena; Wang, Zhaoyue; He, Xiuping (Frontiers in Microbiology, 2022)
Cat8 is an important transcription factor regulating the utilization of non-fermentative carbon sources in Saccharomyces cerevisiae. However, our previous studies found that Cat8 may play a critical role in nitrogen metabolism, but the regulatory mechanism has not been elucidated. In this study, the nuclear localization and analysis of regulatory activity showed that the Cat8 function relies on Snf1 kinase. In the fermentation with glucose or glycerol as carbon sources under phenylalanine (Phe) induction, by comparing the changes of cellular gene expression and Cat8 target gene binding profiles after Cat8 overexpression, enhanced transcription was shown among key genes involved in the Ehrlich pathway (e.g., ARO9, ARO10, and ADH2) and its upstream and downstream related factors (e.g., GAP1, AGP1, GAT1, PDR12, and ESPB6), indicating that Cat8 participated in the regulation of nitrogen metabolism. Moreover, highly active Cat8 interacts with transcriptional activator Aro80 and GATA activator Gat1 coordinately to regulate the transcription of ARO10. Altogether, our results showed that Cat8 may act as a global transcription factor in response to nutritional changes, regulating both carbon and nitrogen utilization. This provides a new insight for us to explore the regulation of cell nutrient metabolism networks in yeast.